Command-Filter-Based Finite-Time Adaptive Control for Nonlinear Systems With Quantized Input - Ma, Jiali; Park, Ju H.; Xu, Shengyuan (IEEE transactions on automatic control, 2021)
This article considers the finite-time adaptive control problem of nonlinear systems with quantized input signal. Compared with existing results, the quantized parameters are unknown and the bound of the disturbance is not required. By utilizing the command filter backstepping method, an adaptive switching-type controller is designed and a novel switching mechanism is also proposed. By regulating the controller parameters online, practical finite-time stability can be guaranteed for the closed-loop system. Finally, a simulation example is given to illustrate the effectiveness of the proposed method.